2020
DOI: 10.3389/fneur.2019.01415
|View full text |Cite
|
Sign up to set email alerts
|

Visual Behavior, Pupil Dilation, and Ability to Identify Emotions From Facial Expressions After Stroke

Abstract: Social cognition is the innate human ability to interpret the emotional state of others from contextual verbal and non-verbal information, and to self-regulate accordingly. Facial expressions are one of the most relevant sources of non-verbal communication, and their interpretation has been extensively investigated in the literature, using both behavioral and physiological measures, such as those derived from visual activity and visual responses. The decoding of facial expressions of emotion is performed by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
3
2
0
Order By: Relevance
“…First, our findings showed that participants with ABI tended to show lower emotional awareness and emotion regulation abilities and more severe depressive symptoms than their matched controls. These results are consistent with previous studies indicating that ABI usually involves deficits in emotional processing ( Cooper et al, 2015 ; Maza et al, 2020 ; Quemada, 2020 ). Similarly, a large body of research highlights the high prevalence rate of psychopathological disturbances in this clinical condition, including depressive symptomatology ( Hackett and Pickles, 2014 ; Scholten et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…First, our findings showed that participants with ABI tended to show lower emotional awareness and emotion regulation abilities and more severe depressive symptoms than their matched controls. These results are consistent with previous studies indicating that ABI usually involves deficits in emotional processing ( Cooper et al, 2015 ; Maza et al, 2020 ; Quemada, 2020 ). Similarly, a large body of research highlights the high prevalence rate of psychopathological disturbances in this clinical condition, including depressive symptomatology ( Hackett and Pickles, 2014 ; Scholten et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…We did not observe impairments in disgust recognition in our patients which is in line with previous ndings (7,31) though also impaired capabilities have been reported (32). In accordance with previous work (6, 21), happiness was the easiest expression to identify compared to negative facial expressions and accurately recognized by our patients.…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings have been reported in a previous study. 5 Stroke patients were not impaired during the processing of disgusted expressions, which is in line with previous findings 6 , 48 though also impaired capabilities have been reported. 49 Stroke patients showed normal response times, which suggests that correct recognitions did not simply result from prolonged evaluation or decision making processes and, hence, that impairments in our stroke cohort were rather mild.…”
Section: Discussionsupporting
confidence: 91%